The mechanism of auxin driving Xanthium strumarium invasion - Zhang, Chang; Cheng, Yuan; Wu, Hai-Long; Han, Xiao; Du, Yu-Xuan; Zhao, Ting-Ting; Qi, Fa-Zhao; Feng, Yu-Long (Frontiers in Plant Science, 2025)
Biological invasion is a critical ecological challenge, exerting profound impacts on ecosystem stability, public health, and economic sustainability. To better understand the successful invasion mechanism, many hypotheses have been proposed. However, the roles of hormones in it are not clear, especially for the differential effects of hormones on invasive and native plants, and its mechanisms. In this study, we hypothesized that there was not only a difference in hormone (auxin) concentration between invasive and native plants but also a difference in the effect of auxin on invasive and native plants. The above characteristics drove the successful invasion of invasive plants. To verify this hypothesis and investigate the mechanism, auxin concentration, and physiological index determination, transcriptomic and metabolomic analyses were performed. Our results showed that the auxin concentration was higher in invasive plants Xanthium strumarium and the growth-promoting effect of auxin on the invader was stronger than its native congener X. sibiricum. Compared with X. sibiricum, the auxin signal transduction in X. strumarium was more strongly activated, and more genes were differentially expressed in response to auxin. Auxin strongly promoted the growth of X. strumarium by enhancing photosynthesis, reducing the resources investment in defense and stress resistance, and promoting cell growth and division. However, the promoting effect of auxin on X. sibiricum was mainly achieved by enhancing photosynthesis. Our results elucidated the mechanism of auxin driving X. strumarium invasion, which contributed to the systematic proposal of the hormone-driven hypothesis.